EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN KOPI ROBUSTA DI KAMPUNG SEED AGUNG DISTRIK MUTING KABUPATEN MERAUKE - Yosefina Mangera; Parjono; Wa Ode Asryanti Wida Malesi; Muhammad Abdul Aziz (JTSL (Jurnal Tanah dan Sumberdaya Lahan))
Land evaluation is the process of assessing the potential of land for various types of use to support planning and management, taking into account the physical and chemical characteristics of the soil. Seed Agung Village, located in the Muting District, has the potential for development for robusta coffee. This research aimed to determine the actual land suitability class for robusta coffee plants in Seed Agung Village, Muting District. The method used in this study was a survey conducted on 2 land types, namely mix gardens and fields. Soil samples were taken to a depth of 0-80 cm, which is the layer of soil that can still be penetrated by roots. Data were collected through direct observation, laboratory analysis, and data processing. Data analysis was conducted by matching the results of field observations and laboratory tests with land suitability criteria for robusta coffee plants based on the Technical Guidelines for Land Evaluation for Agricultural Commodities (Revised Edition 2011). The results showed that the mix gardens and field/field were classified in the marginal suitability class (S3), with limiting factors in the form of water availability (wa) and nutrients (na). The practical implication of the results of this study is as a basis for land management planning, namely irrigation management and water conservation and soil fertility improvement through fertilization.